ThyroSeq v3 for Bethesda III and IV: An institutional experience. Issue 2 (8th October 2020) - Desai, Dimpi; Lepe, Marcos; Baloch, Zubair Wahid; Mandel, Susan J.
Abstract : Background: The ThyroSeq v3 genomic classifier is a commercial molecular test that examines a wide spectrum of genomic alterations in a thyroid fine‐needle aspiration (FNA) sample and reports test results as either negative or positive. The authors report their institutional experience with ThyroSeq v3. Methods: Thyroid FNA specimens diagnosed as either atypia of undetermined significance or follicular lesion of undetermined significance (AUS/FLUS) (Bethesda category III [Bethesda III] according to The Bethesda System for Reporting Thyroid Cytopathology) or follicular neoplasm/suspicious for follicular neoplasm (FN/SFN) (Bethesda IV) that had ThyroSeq v3 results available from December 2017 through October 2019 were retrieved for analysis. FNA diagnoses were correlated with ThyroSeq v3 results and follow‐up histopathology. Results: In total, 415 cases (AUS/FLUS, n = 251; FN/SFN, n = 164) were retrieved: 294 (71%) were reported as ThyroSeq v3‐negative, and 121 (29%) were reported as ThyroSeq v3‐positive. The benign call rate (BCR) of ThyroSeq v3 for AUS/FLUS (82%; 206 of 251 cases) was significantly higher ( P < .001) than that for FN/SFN (BCR, 54%; 88 of 164 cases). Histopathologic follow‐up was available for 127 cases (ThyroSeq v3‐positive, 96; ThyroSeq v3‐negative, 31), of which 57 were benign and 70 were malignant (including noninvasive follicular thyroid neoplasm with papillary‐like nuclear features). The negative predictive value of ThyroSeq v3 was significantly higher for AUS/FLUS (99.5%) than for FN/SFN (95.4%; P < .0294), given malignancy rates of 10% for AUS/FLUS and 30% for FN/SFN. Forty‐five unique combinations of genetic alterations were detected in the operated ThyroSeq‐positive cases, and there were only 5 false‐negative cases, comprised of 4 low‐risk neoplasms. Conclusions: The high BCR of ThyroSeq v3 for AUS/FLUS prevents surgery in a majority of patients. The ThyroSeq v3 genomic classifier reveals the complexity of the genetic signature of indeterminate nodules. Abstract : The benign call rate of the ThyroSeq v3 test is higher for nodules with Bethesda III cytology than for those with Bethesda IV cytology. In 96 surgically resected nodules, 45 unique molecular signatures are observed, demonstrating that the ThyroSeq v3 genomic classifier reveals the complexity of the genetic signature of indeterminate nodules.